Copper-induced ammonia N–H functionalization. Issue 37 (17th February 2016) - Álvarez, María; Álvarez, Eleuterio; Fructos, Manuel R.; Urbano, Juan; Pérez, Pedro J.
Abstract : The Tp Ms Cu core has been found to bind ammonia as well as to promote stoichiometric or catalytic modification of the ammonia N–H bond. Abstract : The activation of ammonia has been achieved with the aid of the Tp Ms Cu core (Tp Ms = hydrotris(3-mesityl-pyrazolyl)borate). Complexes of the general composition Tp Ms Cu(amine) (1–4 ) including the ammonia adduct Tp Ms Cu(NH3 ) (1 ) have been synthesized and fully spectroscopical- and structurally characterized. Coordinated ammonia in1 has been reacted with Ph3 CPF6 yielding Tp Ms Cu(NH2 CPh3 ) (5 ) as a result of N–H cleavage and N–C bond formation. In a parallel manner the catalytic functionalization of ammonia with ethyl diazoacetate leading to glycinate derivatives has been developed with Tp Ms Cu(THF) as the catalyst, in the first example of this transformation with ammonia and a copper-based system.